Molecular Diagnostic Survey of Honey Bee, Apis mellifera L., Pathogens and Parasites from Arkansas, USA - Cleary Dylan; Szalanski Allen L. (Journal of Apicultural Science, 2022)
Managed honey bee populations have fluctuated over the past several decades in the U.S. While a single factor has not been identified for these losses, the interaction between multiple biotic and abiotic stressors have been suggested to be responsible. Of major concern are several invasive parasite and pathogen species as well as colony management. A single honey bee colony often suffers from multiple harmful agents, that may act synergistically and cause greater declines in bee health. We conducted a survey to detect known and lesser-known honey bee parasites and pathogens. While previous research has primarily focused on commercially managed colonies, research is limited to pertaining parasite and pathogen prevalence in hobbyist managed colonies. Molecular diagnostics were used to screen 541 Arkansas (AR) honey bee colonies from 107 hobbyist beekeepers for eight A. mellifera parasite and pathogen species. Colony samples were obtained between 2015–2016 and represented forty-seven of the seventy-five AR counties. Vairimorpha ceranae (11.6% occurrence) and parasite Varroa destructor (49.4% occurrence) were relatively common in AR hobbyist colonies. Interestingly, the lesser-studied pathogenic trypanosome species, Lotmaria passim, was detected in 11.3% of the colonies and widespread in twenty of the forty-seven counties sampled. None of the honey bee pathogens Vairimorpha apis, Spiroplasma apis, S. melliferum, Crithidia mellificae, or the parasitic phorid fly, Apocephalus borealis, were detected in the colonies sampled. This study provides an extensive assessment of the parasite and pathogen species occurring at the AR state-level in hobbyist-managed honey bee colonies.